THE PROBLEM OF UPSET RECOVERY TRAINING IN SCOPE OF AIR FRANCE AF447 ACCIDENT - Pitor, Jan; Havel, Karel (Doprava a spoje, 2012)
This paper summarizes the problem of loss of control in flight accidents in conjunction with inability to recognize and recover stall and aircraft upset situations. It also provides Air France AF447 aircraft accident overview and it's connection to the problem of upset recovery training, together with overview of accident investigation final report outcomes and responses of stakeholders involved.